A Case of End-stage Post-Covid-19 Pulmonary Fibrosis in a Kenyan Hospital (International Journal of Scientific Research and Management (IJSRM), 2024)
Post-COVID-19 pulmonary fibrosis (PC19-PF) is one of the severe manifestations of the “long COVID syndrome,” with a prevalence of about 7%, and is characterized by the presence of persistent fibrotic lung changes (on a CT scan of the lungs) associated with impairment of pulmonary function. Some of the risk factors for PC19-PF include advanced age, the occurrence of acute respiratory distress syndrome (ARDS), the need for supplemental oxygen, mechanical ventilation, smoking, etc. Antifibrotic agents, e.g., pirfenidone and nintedanib, are increasingly being used in the management of PC19-PF with good outcomes, but larger studies on efficacy and benefit are needed. In this study, we present the case of a young woman in a rural Kenyan hospital found to have end-stage PC19-PF needing long-term oxygen therapy to highlight the reality of PC19-PF in the post-COVID-19 clinical era.